Randomized Phase I Trial of Two Different Combination Foscarnet and Ganciclovir Chronic Maintenance Therapy Regimens for AIDS Patients with Cytomegalovirus Retinitis: AIDS Clinical Trials Group Protocol 151 - Jacobson, Mark A.; Kramer, Francoise; Yiannis Bassiakos; Hooton, Thomas; Polsky, Bruce; Geheb, Heidi; O'Donnell, James J.; Walker, John D.; Korvick, Joyce A.; van der Horst, Charles (Journal of Infectious Diseases, 1994)
AIDS patients with newly diagnosed cytomegalovirus (CMV) retinitis who had just completed a 14-day course of ganciclovir induction therapy were randomly assigned to an alternating or concurrent combination regimen of chronic ganciclovir-foscarnet therapy for CMV retinitis. Each regimen used lower weekly cumulative doses of each drug than standard monotherapy maintenance treatment regimens. Dose-limiting toxicity attributable to foscarnet occurred in only 2 (7%) of29 evaluatable patients, and no patients experienced dose-limiting nephrotoxicity. Although absolute neutrophil counts <500 cells/µL occurred in 11 (38%) of 29 patients, all who subsequently used adjunctive granulocyte colony-stimulating factor had severe neutropenia prevented. Severe toxicity of any type and neutropenia, in particular, occurred significantly more frequently in patients assigned to the concurrent treatment regimen. CMV was isolated from none of 21 patients who had urine cultured and from only 1 of 24 who had blood cultured while being treated during the study (median evaluation, 12 weeks). This suggests that combination therapy provides better in vivo antiviral activity in suppressing CMV replication than previously reported with monotherapy regimens.